Molecular detection and profiling of porcine reproductive and respiratory syndrome virus from abattoir slaughtered pigs in Laguna, Philippines - Parayao, Arman M.; Kong, Sokom; Collantes, Therese Marie A.; Baldrias, Loinda R.; Dalmacio, Ida F. (2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) has been spreading and causing major economic losses in intensified swine farms worldwide. In this study, two reverse transcription-polymerase chain reaction (RT-PCR) based detection systems were evaluated for their applicability and sensitivity in detection of the contemporary PRRSV strains in Laguna, Philippines. The collected 388 blood samples from pigs in local abattoirs were pooled and screened for the presence of PRRSV. Out of the 77 pooled samples, 19 were confirmed positive for North American PRRSV genotype, detected using endpoint RT-PCR and subsequent sequence analyses of the RT-PCR products. Qualitative real-time RT-PCR, on the other hand, was able to detect only three of the confirmed local strains. Initial assessment of genetic diversity of the local strains of the virus using the conserved sequences of the open reading frame 6 (ORF6) revealed overall monophyletic topology (80%) in the established phylogenetic tree. Considering the 19 confirmed PRRSV positive cases, higher frequency (73.68%) was observed in commercial farms compared to small-hold farms (26.32%). Sta Cruz, Biñan, San Pedro, Nagcarlan, Siniloan, and Sta Maria were among the municipalities of Laguna with farms positive for PRRSV. All samples were found negative for European genotype and highly pathogenic PRRSV strains.
Keywords: PRRS; Swine diseases; PCR; Genetic techniques